Seasonal variations in bird selection pressure on prey colouration - Zvereva Elena L; Kozlov Mikhail V (Springer, 2022)
The direction and strength of selection for prey colouration by predators vary in space and time and depend on the composition of the predator community. We tested the hypothesis that bird selection pressure on prey colouration changes through the season due to changes in the proportion of naive juvenile individuals in the bird community, because naive and educated birds differ in their responses to prey colours. Bird predation on caterpillar-shaped plasticine models in two boreal forest sites increased sevenfold from early summer to mid-summer, and the time of this increase coincides with the fledging of juvenile birds. In early summer, cryptic (black and green) models were attacked at fivefold higher rates compared with conspicuous (red and yellow) models. By contrast, starting from fledging time, cryptic and conspicuous models were attacked at similar rates, hinting at a lower selectivity by naive juvenile birds compared with educated adult birds. Cryptic models exposed in a group together with conspicuous models were attacked by birds at a threefold lower rate than cryptic models exposed singly, thus supporting the aposematic commensalism hypothesis. However, this effect was not observed in mid- and late summer, presumably due to the lack of avoidance of conspicuous prey by the juvenile birds. We conclude that selection pressure on prey colouration weakens considerably when naive birds dominate in the community, because the survival advantages of aposematic colouration are temporarily lost for both the conspicuous and their neighbouring cryptic prey.